1997
DOI: 10.1002/ana.410420114
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reduction in the posterior cingulate cortex in very early Alzheimer's disease

Abstract: This study investigated cerebral glucose metabolism in very early Alzheimer's disease, before a clinical diagnosis of probable Alzheimer's disease is possible, using [18F]fluorodeoxyglucose positron emission tomography. First, 66 patients with probable Alzheimer's disease with a spectrum of dementia severity (Mini-Mental State Examination score, 0-23) were recruited and studied. Cortical metabolic activity was analyzed topographically using three-dimensional stereotactic surface projections. Regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

96
1,030
3
24

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,574 publications
(1,153 citation statements)
references
References 63 publications
96
1,030
3
24
Order By: Relevance
“…This discrepancy between both profiles suggests that functional changes may be caused partly by remote effects from the morphologically altered hippocampus, while this region would be the site of a compensatory response by neuronal plasticity [8,40,44,51]. The current findings also accord with those of Nestor et al [52] who found that metabolism and atrophy in mesial temporal ROIs were correlated in SD but not in AD.…”
Section: Discussionsupporting
confidence: 84%
“…This discrepancy between both profiles suggests that functional changes may be caused partly by remote effects from the morphologically altered hippocampus, while this region would be the site of a compensatory response by neuronal plasticity [8,40,44,51]. The current findings also accord with those of Nestor et al [52] who found that metabolism and atrophy in mesial temporal ROIs were correlated in SD but not in AD.…”
Section: Discussionsupporting
confidence: 84%
“…The pattern of GM loss was consistent with similar VBM studies of AD Karas et al, 2003), with large areas of GM loss seen in the bilateral inferior and posterior parietal areas, as well as in the bilateral posterior cingulate cortices (PCC). The pattern of hypoperfusion was consistent with similar studies using PET and SPECT (Matsuda et al, 2002;Minoshima et al, 1997), with large areas of hypoperfusion in the right PCC and in the right posterior parietal area. Also a large area of hypoperfusion was seen in the right middle frontal gyrus with some extension into the superior frontal gyrus.…”
Section: Separate Gm and Perfusion Analysessupporting
confidence: 90%
“…We also applied this approach to a multiple modality imaging data set of Alzheimer's disease (AD) (Johnson et al, 2005) which is known to alter both brain structure as well as brain function (Karas et al, 2003;Matsuda et al, 2002;Minoshima et al, 1997). We investigated local changes in gray matter (GM) volume and cerebral perfusion, obtained by T1-weighted structural MRI and arterial spin labeling (ASL) perfusion MRI, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorodeoxyglucose (FDG) positron emission tomography (PET) studies find that persons with Alzheimer's disease (AD) characteristically show preferential and progressive neocortical reductions in measurements of the cerebral metabolic rate for glucose or FDG uptake (Minoshima et al, 1994(Minoshima et al, , 1995(Minoshima et al, , 1997Mielke et al, 1994;Reiman et al, 1996). The posterior cingulate cortex (PCC) appears to be particularly vulnerable (Minoshima et al, 1994(Minoshima et al, , 1997Reiman et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The posterior cingulate cortex (PCC) appears to be particularly vulnerable (Minoshima et al, 1994(Minoshima et al, , 1997Reiman et al, 1996). We have previously reported that cognitively normal, late-middle-aged carriers of the apolipoprotein ε4 allele (APOE4), a common AD susceptibility gene, have functional brain abnormalities in the same neocortical regions as patients with probable AD, prior to the development of cognitive symptoms , and furthermore, younger, 20-to 39-year-old carriers also show significant PET declines in these regions (Reiman et al, 2004), indicating a very early vulnerability in these cortices.…”
Section: Introductionmentioning
confidence: 99%